Transforming transformation in research and teaching at South African universities - Pattman, Rob; Carolissen, Ronelle (Sun Press, 2018)
"What is transformation in contemporary South African higher education? How can it be facilitated through research and pedagogic practices? These questions are addressed in this edited collection by established academics and emerging research students from nine South African universities. The chapters give us access to students' worlds; how they construct, experience and navigate their complex spheres, on and off campus."--Publisher's description